Anesthetic Techniques and Cancer Recurrence after Surgery - Vincenzo Fodale; Maria G. D’Arrigo; Stefania Triolo; Stefania Mondello; Domenico La Torre (The Scientific World Journal)
Many of the most common anesthetics are used in surgical oncology, yet effects on cancer cells are still not known. Anesthesia technique could differentially affect cancer recurrence in oncologic patients undergoing surgery, due to immunosuppression, stimulation of angiogenesis, and dissemination of residual cancer cells. Data support the use of intravenous anesthetics, such as propofol anesthesia, thanks to antitumoral protective effects inhibiting cyclooxygenase 2 and prostaglandins E2 in cancer cells, and stimulation of immunity response; a restriction in the use of volatile anesthetics; restriction in the use of opioids as they suppress humoral and cellular immunity, and their chronic use favors angiogenesis and development of metastases; use of locoregional anesthesia compared with general anesthesia, as locoregional appears to reduce cancer recurrence after surgery. However, these findings must be interpreted cautiously as there is no evidence that simple changes in the practice of anesthesia can have a positive impact on postsurgical survival of cancer patients.